The Role of Plasma Osmolarity in the Mortality of Patients with Covid-19 - Indiastari, Dewi; Candradikusuma, Didi; Sutanto, Heri; Budiarti, Niniek; Samsu, Nur (Fakultas Kedokteran Universitas Brawijaya, 2024)
Covid-19 (Coronavirus disease 2019) is a new infectious disease that attacks the respiratory tract and is caused by severe acute respiratory syndrome coronavirus 2 (SARSCoV-2), causing multiorgan failure, often requiring temporary support such as the use of a ventilator or hemodialysis equipment. This condition is related to an imbalance in fluid distribution associated with changes in osmolarity or hyperosmolarity. This research aims to explain the role of plasma osmolarity in Covid-19 patients at dr. Saiful Anwar Hospital, Malang, in patient outcomes, especially death outcomes. The sample for this study was 205 medical records of Covid-19 patients, recorded from September 2021 to May 2022. This study used a retrospective cohort design to describe plasma osmolarity in Covid-19 patients and the outcome of hospitalized patients. There were 205 patient data obtained, with 85 patients dying aged <65 years. Sixty-eight patients of Covid-19 with comorbidities (DM, HT, AKI, CKD, combination) died. There was no difference in plasma osmolarity for living and deceased patients. Repeated plasma osmolarity (retest) had a good degree of accuracy in predicting the outcome of Covid-19 patients, where sensitivity was 71.3% and specificity was 73.4% at a cut-off value of 277.32mOsm/L. The repeat plasma osmolarity value of ≥277.32 had a PPV value of 75%, while plasma osmolarity <277.32 had an NPV value of 69.3%. The OR value was 6.77, meaning that Covid-19 patients with repeated plasma osmolarity levels ≥277.32 would have 6.77 times the risk of mortality compared to Covid-19 patients with repeated plasma osmolarity levels <277.32.